Design Thinking Method: Qurban Animal Application in Facing Eid Al-Adha in Indonesia - Emiya Fefayosa Br Tarigan; Rahmat Yasirandi; Fahdah Almarshad; Isa Mulia Insan; Novian Anggis Suwastika (My University, 2022)
Technological innovation in Indonesia has brought many advantages. Religious activities are no exception. Islam, as Indonesia’s majority religion, is one of those affected by the positive impact. Many technological innovations have helped the activities of Muslims in Indonesia. This includes the Eid Al-Adha event as well as the case study proposed in this study. By using the Design Thinking Approach, this study succeeded in proposing an application related to sacrificial animals. The application prototype is thriving with a proper acceptance level. This study conducted System Usability Scale Testing for 46 participants at the test stage, with SUS’s score of 78.07, means the proposed prototype is included in the “Good” Grade and “Acceptable” category. This means the fulfilment of the needs and functionality of prospective users has been successfully provided.
Keywords: Educational Methods and Impacts; Blockchain Technology in Education and Learning; Education and Character Development